Second-hand harms of alcohol use in urban Chinese university students: A study from Hong Kong. (30th September 2020) - Kim, J; Chan, R H W; Leung, K L; Chan, K Y M; Chung, R Y; Fong, B; Sumerlin, T S; Siu, S; Lee, J J
Abstract: Background: Although second-harms alcohol harms, harms caused by the drinking of others, may contribute significantly to the public health burden of alcohol, these harms are an understudied area of public health research. This study aims to examine second-hand alcohol harms in among urban Chinese university students residing on campus who are were previously identified as a high risk group for alcohol misuse. Methods: A cross-sectional study was conducted among hostel residents in two Hong Kong universities (n = 1455) using self-administered, anonymous surveys. We examined the prevalance and the factors associated with second-hand alcohol harms this population using multivariable regression analysis. Results: Approximately 2/3 of the university residents experienced at least one second-hand drinking harm in the past year while 1/5 experienced 4 or more harms. The harms reported were: 1) inconveniences/disturbances (46.2%), psychological distress/anxiety/depression (32.9%), home arguments (28.3%), conflicts/arguments/insults in public (25.3%), worsened productivity/academics (22.2%), property damage/monetary loss (13.2%), accidents/injury/assault (11.7%) and having to deal with authorities/law enforcement (11.5%). Only 9.1% reported these harms to authorities. Participation in drinking games (OR = 1.44), having drinking roomates (OR = 1.37) or drinking romantic partner (OR = 1.89) were independently associated with likelihood of second-hand alcohol harms (p < 0.05). Conclusions: Although southern China is a low alcohol consumption region, there is a high prevalence of second-hand alcohol harms among university dorm residents. Universities in the region should rectify the near absence of alcohol-related topics in university health promotion. Key messages: Harms from the drinking of others is a commonplace but underappreciated phenomenon among university campus residents. University health promotion in the region should include alcohol harms reduction topics.